2013
DOI: 10.1016/j.jnnfm.2012.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Numerical investigations of polyester coextrusion instabilities

Abstract: Interfacial instabilities occurring in the coextrusion process of molten polymers have been widely studied. The theoretical work based on the stability of 2D Poiseuille multilayer flows (invariant along the flow motion) have pointed out the convective nature of this instability (it is either amplified or damped in the flow direction). This behaviour has been confirmed by experimental observations. As this instability is purely elastic (the Reynold number in coextrusion process is very small), it is necessary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The figure shows a kind of secondary flow that is a reflection of velocity X and velocity Y shown in Fig. a and b. Dooely studied the secondary flow caused by polymeric viscoelasticity in a rectangle channel with constant cross‐section and discovered that the velocity component perpendicular to the flow direction was approximately two orders of magnitude lower than that along the flow direction in this secondary flow process. However, in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The figure shows a kind of secondary flow that is a reflection of velocity X and velocity Y shown in Fig. a and b. Dooely studied the secondary flow caused by polymeric viscoelasticity in a rectangle channel with constant cross‐section and discovered that the velocity component perpendicular to the flow direction was approximately two orders of magnitude lower than that along the flow direction in this secondary flow process. However, in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, most studies concerning layer interface deformation concentrate on traditional coextrusion processing, which shows relatively simple flow behavior . Experimental and numerical analysis methods were widely used to study these problems in the first 20 years of development; however, these methods were gradually replaced by the finite element method (FEM), which is a powerful tool for easily and quickly studying the rheology of polymer melts in a mold.…”
Section: Introductionmentioning
confidence: 99%
“…The coextrusion of two polyesters in the final section of a coat-hanger die with a convergent gap and a constant width was considered. The two polyesters had different behaviors, one was Newtonian and the other one viscoelastic and shear-thinning, described by a multi-mode Oldroyd-B model ([ 38 ]). A small amplitude perturbation is imposed on one of the two inlet flows and the propagation of this disturbance along the flow is computed.…”
Section: Miscellaneous Applications Of Poiseuille Coextrusion Computa...mentioning
confidence: 99%
“…Because of the complex rheology of the polymers being coextruded several type of instabilities exist, including viscous instabilities from viscosity mismatch, elastic instabilities from time constant mismatch between layers exacerbated by the sec-ondary flows present in viscoelastic fluids, and temperature and surface tension gradient driven instabilities. Alarge body of literature has been devoted to understanding instabilities associated with both viscosity (see Alba et al, 2011 for as ummary of the literature) and elastic effects (see Mahdaoui et al, 2013 for as ummary of this literature.) It has been found that these instabilities are convective in nature meaning that they either grow or decay in the flow direction.…”
Section: Linear Stability Analysismentioning
confidence: 99%